AMELIORATIVE EFFECT OF PHOENIX DACTYLIFERA ON ADVERSE EFFECTS OF LINEZOLID IN MALE ALBINO RATS - ABDO SAID, MAHMOUD AHMED; AZIZ, SAYED A.; ELNABTITY, SAMEH M. (International Journal of Applied Pharmaceutics, 2019)
Objective: This study aimed to investigate the adverse effects of linezolid (LZD) on biochemical and hematological parameters and some organs including bone marrow, brain, and kidneys and to investigate the possibility of methanolic extract of Phoenix dactylifera (MEPD) to counteract the adverse effects of LZD. Methods: Forty-eight adult male albino rats were allocated into four equal groups (each of 12 animals). The first group received Tween 80 orally. The second group received was given 0.5 ml of LZD suspension 4% in Tween 80 (100 mg/kg body weight) orally. The third group received the same dose of LZD suspension followed by 1 ml of MEPD orally. The rats in the last group were given 1 ml of MEPD (1000 mg/kg body weight) orally. Rats were sacrificed and blood samples were collected for hematological and biochemical study. Femur bones, brain, and kidneys were dissected and kept in a jar containing 10% formalin to perform the histopathological investigation. Results: The dose of LZD administered for 14 successive days induced a mild-to-moderate hematological abnormalities including decrease in hemoglobin content (7.88±0.18 g/L) on day-1 post-treatment. Significant increase in serum urea (59.75±0.85) and serum creatinine was observed (1.89±0.04). On day-14 post-treatment, LZD induced mild-to-moderate cellular abnormalities in bone marrow, brain, and kidneys. The concurrent oral administration of MEPD and LZD for the same period corrected the hematological, biochemical, and histopathological alterations induced by LZD. Conclusion: It was concluded that MEPD clearly ameliorated these damaging effects induced by LZD.